2008
DOI: 10.1557/proc-1126-s08-10
|View full text |Cite
|
Sign up to set email alerts
|

In situ Synchrotron X-ray Studies of Dense Thin-Film Strontium-Doped Lanthanum Manganite Solid Oxide Fuel Cell Cathodes

Abstract: Using a model cathode-electrolyte system composed of epitaxial thin-films of La1-xSrxMnO3-δ (LSM) on single crystal yttria-stabilized zirconia (YSZ), we investigated changes in the cation concentration profile in the LSM during heating and under applied potential using grazing incidence x-rays. Pulsed laser deposition (PLD) was used to grow epitaxial LSM(011) on YSZ(111). At room temperature, we find that Sr segregates to form Sr enriched nanoparticles and upon heating the sample to 700°C, Sr is slowly reincor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 7 publications
3
21
1
Order By: Relevance
“…Most literature reports demonstrate a change in the degree of strontium enrichment that depends on the thermal history of the sample. Of particular significance to the present work are results of Fister et al [16] and Chang et al [17], both of whom demonstrate a decrease in surface strontium enrichment as the temperature of dense LSM films increases from 300 C up to 900 C.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Most literature reports demonstrate a change in the degree of strontium enrichment that depends on the thermal history of the sample. Of particular significance to the present work are results of Fister et al [16] and Chang et al [17], both of whom demonstrate a decrease in surface strontium enrichment as the temperature of dense LSM films increases from 300 C up to 900 C.…”
Section: Discussionsupporting
confidence: 48%
“…Strontium enrichment of the surface of LSM perovskites has been well-documented using a variety of techniques: Auger electron spectroscopy (AES) [15], total reflection x-ray fluorescence (TXRF) [16,17], x-ray photoelectron spectroscopy (XPS) [1,18,19], various methods of soft x-ray spectroscopy [20], and chemical analysis of an LSM surface etched by an acid solution. 3,13 Similar enrichment of the Sr:La ratio was reported with the perovskite La 0.6 Sr 0.4 CoO 3 (LSC) by Kubicek et al using time-of-flight secondary ion mass spectroscopy (ToF-SIMS) on an LSC thin film as well as chemical analysis of the LSC surface etched by an acid solution [21].…”
Section: Discussionmentioning
confidence: 99%
“…13 Since cathode performance may depend quite sensitively on surface composition, finding the cause of Sr segregation is of significant interest. [14][15][16] Kinetic demixing is a general phenomenon 17 in compound oxides that can occur anytime there is a chemical potential gradient in O. [14][15][16] Kinetic demixing is a general phenomenon 17 in compound oxides that can occur anytime there is a chemical potential gradient in O.…”
mentioning
confidence: 99%
“…Cathode performance is sensitive to changes in the available surface area for oxygen reduction and to changes in the cathode's specific surface catalytic activity for oxygen reduction through changes in the surface composition. Previous studies have shown that cation segregation can occur within thin films and bulk samples of common SOFC cathode materials such as La 1 − x Sr x MnO 3 (LSM) [2][3][4][5][6][7][8][9][10][11] and La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3 (LSCF) [11][12][13][14][15][16][17][18][19]. The degree to which certain cations build up at the electrode/ gas surface depends upon the temperature and the oxygen partial pressure.…”
Section: Introductionmentioning
confidence: 99%